SILAC-based phosphoproteomics reveals new PP2A-Cdc55-regulated processes in budding yeast. Issue 5 (24th May 2018) - Baro, Barbara; Játiva, Soraya; Calabria, Inés; Vinaixa, Judith; Bech-Serra, Joan-Josep; de LaTorre, Carolina; Rodrigues, João; Hernáez, María Luisa; Gil, Concha; Barceló-Batllori, Silvia; Larsen, Martin R; Queralt, Ethel
Abstract: Background: Protein phosphatase 2A (PP2A) is a family of conserved serine/threonine phosphatases involved in several essential aspects of cell growth and proliferation. PP2A Cdc55 phosphatase has been extensively related to cell cycle events in budding yeast; however, few PP2A Cdc55 substrates have been identified. Here, we performed a quantitative mass spectrometry approach to reveal new substrates of PP2A Cdc55 phosphatase and new PP2A-related processes in mitotic arrested cells. Results: We identified 62 statistically significant PP2A Cdc55 substrates involved mainly in actin-cytoskeleton organization. In addition, we validated new PP2A Cdc55 substrates such as Slk19 and Lte1, involved in early and late anaphase pathways, and Zeo1, a component of the cell wall integrity pathway. Finally, we constructed docking models of Cdc55 and its substrate Mob1. We found that the predominant interface on Cdc55 is mediated by a protruding loop consisting of residues 84–90, thus highlighting the relevance of these aminoacids for substrate interaction. Conclusions: We used phosphoproteomics of Cdc55-deficient cells to uncover new PP2A Cdc55 substrates and functions in mitosis. As expected, several hyperphosphorylated proteins corresponded to Cdk1-dependent substrates, although other kinases' consensus motifs were also enriched in our dataset, suggesting that PP2A Cdc55 counteracts and regulates other kinases distinct from Cdk1. Indeed, Pkc1 emerged as a novel node of PP2A Cdc55 regulation, highlighting a major role of PP2A Cdc55 in actin cytoskeleton and cytokinesis, gene ontology terms significantly enriched in the PP2A Cdc55 -dependent phosphoproteome.